Antimicrobial study of chloroform fraction from the leaves of entada spiralis ridl. - Rachmadita, Fitri; Martati, Erryana; Syed Mohamad, Sharifah Nurul Akilah; Mat So'ad, Siti Zaiton (IIUM Press, 2021)
Stigmatising people with a history of substance use disorders (PHSUDs) is discriminatory, causes harm by hindering access to health services and promotes relapse. It jeopardises the preservation of Maqasid Al-Shariah, particularly the protection of life and well-being. Experiential education (EE) is a potential strategy to overcome stigma through direct experience with PHSUDs. This study aimed to identify stigmatised views of PHSUD's held by pharmacy students and, in accord with Maqasid Al-Shariah, the effectiveness of EE in changing those views